INACTIVATION EFFECTS OF NEGATIVE PRESSURES BY A METAL BERTHELOT TECHNIQUE ON BACTERIA SOLUTIONS: Received: 27th June 2022; Revised: 8th September 2022, 18th November 2022, 14th November 2022; Accepted: 19th November 2022 - Hiro, Kazuki; Imanishi, Momoko; Fukuoka, Hiroshi; Itsuki, Ayuko; Kotake, Hiroki (MATTER: International Journal of Science and Technology, 2022)
Bacterial solutions are anticipated to be inactivated under absolute liquid negative pressures much lower in magnitude than positive ones. The pressures, however, have been hard to be produced by experiments because liquids form cavities easily through heterogeneous nucleation. To investigate the anticipation, solutions including two kinds of bacteria, namely Bacillus subtilis and Escherichia coli, were exposed to negative pressures repeatedly by a metal Berthelot tube which was designed newly. Then, numbers of colonies in bacteria which were cultured by a paper strip method and an agar dilute plate one were counted. Numbers of colonies which underwent negative pressures were less than those for non-treatment, and reduction rates of colonies increased with numbers of repetition.